Internet of things-based electric switchboard panel using mobile application as control mechanism - Raian Dhey Carreon, Miguel David, Krishia Gercayo and Joshua Rhys Meneses. 4 0 16; 5
ABSTRACT: The emerging Internet-of-Things (IOT) technology have already made an enormous impact on how an individual managed hi daily activities. With large number of people having mobile devices and connection to the internet, granting same level of connectivity to the devices used for personal or business will bring us to the next era of the information age. This study introduced both internet of things and mobile application as mechanisms of controlling appliances inside home residences or buildings remotely. Wirelessly connecting and communicating each devices and appliances using Message Queuing Telemetry Transport protocol via Mosquito, an open-source message broker in sending triggering signals to Espressif ESP 12E microcontroller actuated the corresponding relays to turn on or off the devices or appliances effectively. However, using internet as a medium requires a reliable internet connection that varies among different locations in the Philippines. To solve this problem, the users can override the control of appliances via Short Message Services (SMS) when there is no available internet connection. Proper configuration of the logical layout of electrical panel board in the mobile apps resulted to effective remote control and monitoring of devices and appliances inside home residences or buildings anywhere and anytime. Moreover, this study also allowed the users to monitor real-time temperature changes and energy consumption.
Thesis: (BS in Computer Engineering) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2